Hypermobility of Joints - Beighton, Peter H.; Grahame, Rodney; Bird, Howard; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Hypermobility of Joints 4th Edition follows the same format as its successful predecessors. The aim of which was to provide an overview of hyperlaxity of joints and this edition follows that aim by describing the most recent research and new developments in biochemistry, as well as providing practical advice on clinical features and management. Hypermobility of Joints 4th Edition provides illustrative case histories, a review of hypermobility in the performing arts and sports and an outline of heritable hypermobility syndromes. This book is a valuable reference tool for a wide number of specialties, although it will particularly be of interest to rheumatologists, orthopedic surgeons and medical geneticists.
Introduction to Hypermobility -- Assessment of Hypermobility -- Molecular Basis of Hypermobility -- Biomechanics of Hypermobility: Selected Aspects -- Musculoskeletal Features of Hypermobility -- Extra-articular Manifestations of Hypermobility -- Illustrative Case Histories -- Hypermobility in Performing Arts and Sport -- Heritable Hypermobility Syndromes.
Keywords: Medicine; Orthopedic surgery; Rheumatology; Medicine & Public Health; Rheumatology; Surgical Orthopedics